Penerapan Good Manufacturing Product Keciput” Prizzto” Jabon Kabupaten Majokerto - Ahmad N; Anita; Ninis Oktaviani KT; Ekky RB Herlambang; Ainul Yaqin; Panca Roozika; Naili Ismawati (Hikamatzu | Journal of Multidisciplinary, 2024)
Keciput is a wave-shaped pastry made from sticky rice flour, sesame seeds, eggs, granulated sugar, salt and water, small in size and has no filling. The purpose of service at CV. Kholifah Food to find out how keciput is made based on GMP assessment standards. The method used is observation. The result is that CV. Kholifah Food is a keciput producer based in Jabon, Mojokerto District, founded in 1998 with the PRIZZTO brand and has implemented GMP standards well so that the products are very safe for consumption and distributed as SME products that have food safety